2017
DOI: 10.1038/nmeth.4228
|View full text |Cite
|
Sign up to set email alerts
|

Internally tagged ubiquitin: a tool to identify linear polyubiquitin-modified proteins by mass spectrometry

Abstract: Ubiquitination controls a plethora of cellular processes. Modifications by linear polyubiquitin have so far been linked with acquired and innate immunity, lymphocyte development and genotoxic stress response. Until now, a single E3 ligase complex (LUBAC), one specific deubiquitinase (OTULIN) and a very few linear polyubiquitinated substrates have been identified. Current methods for studying lysine-based polyubiquitination are not suitable for the detection of linear polyubiquitin-modified proteins. Here, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 60 publications
0
55
0
Order By: Relevance
“…Proteins were in‐gel digested by endoproteinase LysC (SILAC experiments) or trypsin and extracted peptides were desalted using C18 StageTips . LC‐MS/MS analyses were performed on an EASY‐nLC 1200 system (Thermo Fisher Scientific, Karlsruhe, Germany) coupled with an LTQ Orbitrap Elite mass spectrometer (Thermo Fisher Scientific) as described elsewhere with slight modifications: peptide mixtures were separated using a 127 segmented gradient of 10–33–50–90% of HPLC solvent B (80% acetonitrile in 0.1% formic acid) in HPLC solvent A (0.1% formic acid) at a flow rate of 200 nL·min −1 . In each scan cycle, the 15 most intense precursor ions were sequentially fragmented using collision‐induced dissociation.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were in‐gel digested by endoproteinase LysC (SILAC experiments) or trypsin and extracted peptides were desalted using C18 StageTips . LC‐MS/MS analyses were performed on an EASY‐nLC 1200 system (Thermo Fisher Scientific, Karlsruhe, Germany) coupled with an LTQ Orbitrap Elite mass spectrometer (Thermo Fisher Scientific) as described elsewhere with slight modifications: peptide mixtures were separated using a 127 segmented gradient of 10–33–50–90% of HPLC solvent B (80% acetonitrile in 0.1% formic acid) in HPLC solvent A (0.1% formic acid) at a flow rate of 200 nL·min −1 . In each scan cycle, the 15 most intense precursor ions were sequentially fragmented using collision‐induced dissociation.…”
Section: Methodsmentioning
confidence: 99%
“…The e-lysine (K) residues in the target serve as the typical Ub acceptors, forming isopeptide bonds with the C-terminal glycine carboxy group of ubiquitin (Okumoto et al, 2011). Ubiquitin also modifies itself at each of its seven lysine residues (K6, K11, K27, K29, K33, K48 and K63; Peng et al, 2003) or its N-terminal residues (Kliza et al, 2017). K48-linked poly-ub is the predominant (> 50%) linkage type functioning in directing targets to UPS for degradation (Hershko et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, by applying an internally STREP II‐tagged ubiquitin (INT‐Ub.7KR) approach, Kliza et al. found that LUBAC‐mediated TRAF6 linear polyubiquitination is crucial for NF‐κB signaling …”
Section: Linear Polyubiquitination Plays Pivotal Roles In Inflammatormentioning
confidence: 99%
“…Recently, Kliza et al. utilized internally STREP II‐tagged ubiquitin (INT‐Ub.7KR) to confirm the regulatory role of linear polyubiquitination in the NF‐κB signaling pathway and to discover new linear ubiquitination targets . This internally tagged ubiquitin is a simple and powerful tool for studying the function of linear ubiquitin chains.…”
Section: Tools For Studying Atypical Polyubiquitinationmentioning
confidence: 99%